Independent influence of type 2 diabetes on reduced cardiopulmonary fitness in patients after percutaneous coronary intervention: a cross-sectional study - Yutao Liu; Nan Li; Suhui Zhang; Yan Feng; Ying Zhang; Yong Shao; Jiahui Wu (Scientific Reports)
Abstract Previous studies have found a significant association between type 2 diabetes (T2DM) and impaired cardiopulmonary fitness (CRF); however, little evidence was shown in patients after percutaneous coronary intervention (PCI). This study aimed to evaluate the independent effects of T2DM on CRF in patients who have undergone successful percutaneous coronary intervention (PCI) and received guideline-directed medical therapy. Additionally, we explored whether this association is influenced by factors such as demographic features, physical activity level, duration of diabetes, time from index PCI, and history of occlusion myocardial infarction. We retrospectively analyzed data from post-PCI patients who consecutively visited the Cardiac Rehabilitation Center at Beijing Anzhen Hospital between September 2023 and July 2024. To isolate the impact of T2DM on cardiovascular fitness, we implemented strict exclusion criteria for confounding comorbidities, particularly heart failure. Cardiorespiratory fitness was quantified through gold-standard measures: peak oxygen uptake (VO2max) and metabolic equivalents (METs). Baseline characteristics were compared between patients with T2DM and non-diabetic patients (DM group vs. non-DM group). A multivariable regression model was used to evaluate the independent effect of T2DM on CRF, adjusting for confounding factors such as demographic features, physical activity level, duration of diabetes, time since index PCI, and residual comorbidities. Subgroup analyses and interaction tests were performed to assess the impact of T2DM across different subgroups. 201 patients (150 non-DM and 51 DM patients) were included in the final analysis. Hypertension was significantly more prevalent in DM patients (68.6 vs. 42.7%, p = 0.001), while other comorbidities, anthropometric measurements, lifestyle factors, and time from index PCI showed no significant differences between groups (all p > 0.05). Multivariate logistic regression analyses demonstrated significant negative associations between T2DM and both VO2max and METs. After adjusting for basic demographic and lifestyle factors (Model 1), T2DM was inversely associated with VO2max (β=−98.3, 95% CI −193.4 to −3.3, p = 0.044) and METs (β=−0.4, 95% CI −0.8 to −0.0, p = 0.05). These negative associations remained robust and became stronger in Model 2, which further adjusted for physical activity status, hypertension, hyperlipidemia, history of occlusion myocardial infarction, time from index PCI, DM duration, and using beta-blockers, showing more pronounced inverse relationships with both VO2max (β=−212.3, 95% CI −389.4 to −35.3, p = 0.02) and METs (β=−0.9, 95% CI −1.6 to −0.2, p = 0.014). Subgroup analyses indicated consistent inverse associations, with no significant effect modification based on sex, age, body mass index (BMI), time since the index PCI, physical activity status, or a history of occlusion myocardial infarction. Our study demonstrates that T2DM is an independent negative predictor of CRF in post-PCI patients, with consistent findings across various subgroups and robust results after adjusting for confounding factors. These findings underscore the importance of CRF assessment in post-PCI patients and highlight the need for targeted interventions to improve CRF in individuals with T2DM.